Evaluating the germination potential of Pterocarpus angolensis and Strychnos cocculoides with tissue culture techniques - Heita, Hleni Twiitileni Ndeshipanda (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScFor)--Stellenbosch University, 2018.